2018
DOI: 10.1115/1.4040319
|View full text |Cite
|
Sign up to set email alerts
|

Double Pulse Low-Frequency Modulation for High-Power Double-Wire Pulsed GMAW

Abstract: A double pulse low-frequency modulation method was proposed to improve heat input control and enhance weld quality during high-power double-wire pulsed gas metal arc welding (GMAW). By constructing a mathematical model, relationships between parameters of double pulse low-frequency modulation and energy input were analyzed. A correction coefficient was added to overcome physical characteristics of charging and discharging in a welding circuit. Thus, qualitative relationships between parameters of double pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In addition, it can be seen that the work [49] has some similar points to the work [39], both of the two works introduced high-frequency modulation to the original current waveform. Actually, the trailing current in the Figure.…”
Section: Improvement Of Process Control Of the Double-wire Gmaw Processmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, it can be seen that the work [49] has some similar points to the work [39], both of the two works introduced high-frequency modulation to the original current waveform. Actually, the trailing current in the Figure.…”
Section: Improvement Of Process Control Of the Double-wire Gmaw Processmentioning
confidence: 85%
“…To improve the heat delivery and quality of weld bead, Wu et al [39] proposed to add a double pulses low-frequency modulation for a high-power double-wire GMAW process. The double pulses included a consecutive weak and strong pulse, as shown in Figure .4.…”
Section: Improvement Of Process Control Of the Double-wire Gmaw Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [18] introduced a dual-wire DP-GMAW with a median current waveform based on the conventional rectangular pulse and found that changed the median current, the average welding current also changed. The research on increasing the stirring effect of the molten pool mainly includes low-frequency [19, 20], current amplitude [21], and additional technology [22]. Liu et al [23] observed the change of the molten pool profile during the DP-GMAW welding process and found that the molten pool profile changes periodically with the change of low-frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The overlap between these points depends on the pulse frequency and the welding speed [1]. Based on the information available in the literature, there are numerous advantages attributed to this technique, including greater control over the molten pool [2,3], reducing the heat input [4], residual stresses and distortions [4,5] and grain refinement in the molten zone [2][3][4]6].…”
Section: Introductionmentioning
confidence: 99%